2015
DOI: 10.1093/mnrasl/slv175
|View full text |Cite
|
Sign up to set email alerts
|

LoCuSS: Testing hydrostatic equilibrium in galaxy clusters

Abstract: We test the assumption of hydrostatic equilibrium in an X-ray luminosity selected sample of 50 galaxy clusters at 0.15 < z < 0.3 from the Local Cluster Substructure Survey (LoCuSS). Our weak-lensing measurements of M 500 control systematic biases to sub-4 per cent, and our hydrostatic measurements of the same achieve excellent agreement between XMM-Newton and Chandra. The mean ratio of X-ray to lensing mass for these 50 clusters is β X = 0.95 ± 0.05, and for the 44 clusters also detected by Planck, the mean ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 40 publications
11
111
1
Order By: Relevance
“…) than both the Smith et al (2016) lensing determination and the Rines et al (2016) determination, also based on velocity dispersions; both determinations favor little or no mass bias. However, we agree within 1σ with the results from WtG (von der Linden et al 2014), the CCCP (Hoekstra et al 2015), 13 There is some confusion in the nature of these corrections.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…) than both the Smith et al (2016) lensing determination and the Rines et al (2016) determination, also based on velocity dispersions; both determinations favor little or no mass bias. However, we agree within 1σ with the results from WtG (von der Linden et al 2014), the CCCP (Hoekstra et al 2015), 13 There is some confusion in the nature of these corrections.…”
Section: Discussionmentioning
confidence: 90%
“…13 Smith et al (2016) use three sets of independent mass measurements to study the departures from hydrostatic equilibrium in the Local Cluster Substructure Survey (LoCuSS) sample of 50 clusters at z 0.15 0.3 < <…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okabe & Smith (2015) presented weak-lensing mass measurements for the LoCuSS sample and found results ∼10% lower than WtG, but in good agreement with CCCP and CLASH (Donahue et al 2014). While WtG and CCCP indicate a bias of the order of 20−30% in the mass calibration adopted by the Planck team (Planck Collaboration XI 2011), Smith et al (2016) showed that the LoCuSS data are consistent with no bias, depending on the method adopted to compute the sample average. No consensus has thus been reached on the true value of the hydrostatic bias (see also Sereno & Ettori 2015;Applegate et al 2016).…”
Section: Comparison With Previous Measurementsmentioning
confidence: 98%
“…The hydrostatic bias necessary to reconcile the Planck data sets is a factor of two larger than the expectation from simulations. Recently there has been a significant effort to characterize the bias using other observables that are insensitive to the hydrodynamical state of the ICM, primarily gravitational weak lensing (von der Linden et al 2014;Hoekstra et al 2015;Smith et al 2016).…”
Section: Introductionmentioning
confidence: 99%